The Study of Some Flower Characteristics and Active Medical Compounds in the Coriander Plant (Coriandrum sativum L.) under the Effect of Phosphorus and Tryptophan and the Overlapping between Them (Journal of the College of Basic Education, 2020)
A field experiment was conducted in the botanical garden of the Department of Science-College of Basic Education/Al-Mustansiriyah University for the winter growing season 2018-2019 to know the effect of the increasing concentrations and levels of each of the growth organizer tryptophan and the phosphorus fertilizer and the overlap between them on some shape and physiological characteristics of coriander plant (Coriandrum sativum L.). The coriander seeds were planted on 15/11/2018 with conducting all agricultural processes including irrigation and fertilization, removing the bushes and following-up the growth of the plant until the harvest date.The phosphorus fertilizer was added in three levels (0, 30 and 60) kg.h-1 as well as adding three concentrations of tryptophan acid (0, 5 and 10)mg.L-1. The experiment was designed according to the Randomized Complete Block Design (R.C.B.D), and thus it included (27) experimental units, each with an area of one square meter, and it became a factor experiment (3×3×3).The results and the findings showed that adding the phosphorus with a mean of 60kg.h-1 led to an increase in the number of main branches with a ratio of 21.71%, and that adding it with a ratio of 60 kg.h-1 led to an increase in the number of sub branches with a ratio of 21.85% and a ratio of oil 13.18%, as well as there was no significant effect when adding the phosphorus at the qualitative density and the refractive index. Also, spraying with the tryptophan acid at the concentration of 5 mg.L-1 resulted in an increase in the number of main branches with a ratio of 15.38%, sub branches with a ratio of 15.55% and oil 20.68%, as well as there was no significant effect at the qualitative density and the refractive index when adding the tryptophan. The binary intermingling between 60kg.h-1 phosphorus and 5 mg.L-1 tryptophan led to an increase in the number of main branches with a ratio of 46.88%, sub branches 46.95% and oil ratio 52.90%, as well as there was no significant effect at the qualitative density and the refractive index. The results of the chromatographic examination and diagnosis using High Performance Liquid chromatography (HPLC) showed the diagnosis of eight compounds of coriander volatile oil including (camphor, limonene, cis–dihytorxycarvone, Broneal, Linalool, Neral, Geranyl acetate, coumarin).